Pengukuran Efektivitas Kinerja Excavator pada Pengupasan Overburden (OB) Menggunakan Metode Overall Equipment Effectiveness (OEE): Studi Kasus di Pit 7 PT XYZ Kintap, Kalimantan Selatan - Sangaji Agung Wicaksono; Utaminingsih Linarti (Universitas Katolik Parahyangan, 2021)
Based on production data of overburden (OB) stripping at Pit 7 PT XYZ in February 2019, productivity of the excavators doesn’t reach the desired target. To find out the potential for increased productivity and effectiveness of using excavators, it’s necessary to do an analysis using the Overall Equipment Effectiveness (OEE) method. OEE is a performance measurement tool that has the ability to identify the root of the problem and it’s causative factors so that improvement efforts are more focused. The parameters used in the calculation of OEE value are: Availability, Utilization, and Productivity Index. Based on the result of data processing, the OEE value were 56,00% for excavator EX2313 and 34,19% for excavator EX2325. This means that the OEE value hasn’t been able to meet the world class standard OEE value in medium category, namely 60%. Improvement are made by reducing lost work time but obstacles can be avoided, so as to increase utilization. The proposed improvement provide increased in the OEE value were 12,73% for excavator EX2313 and 11,61% for excavator EX2325. This shows that the OEE value of PC800 with number EX2313 reaches the world class standard in medium category or productivity can be considered reasonable, namely 68,73%. Meanwhile, the OEE value of PC800 with number EX2325 still doesn’t reach the world class standard in medium category, namely 45,80%.